Hubungan antara Dukungan Suami dengan Mekanisme Koping Istri yang Menderita Kista Ovarium di Purwokerto - Triyanto, Endang (Jurnal Keperawatan Soedirman, 2010)
Disorders of the women ovary can lead to impaired growth and development as well as maturity of the ovum, so that it could make high risk for women to become infertile. The most commonly gynecologycal problem occurred in women is ovarian cysts. This situation become worst if her husband doesn’t give support and tend to blame his wife. The purpose of this study is to describe correlation between the support given by husband with coping mechanisms his wife who suffered from ovarian cysts. Sampling techniques performed in this study is purposive sampling. Respondents were ovarian cyst women who live in Purwokerto during April to June 2009. The result of this study show there is a relationship between support given by husband to his wife’s coping mechanisms who suffered from ovarian cysts (p=0.016 at Confident Interval 95%). Family support can help improve family coping mechanisms. Husband can provide emotional support and advice on positive coping strategies. Husband should provide good support to his wife's health condition or illness.